Housing finance and development; an analysis and a programme for reform - Merrett, A. J.; Sykes, Allen (London : Longmans, 1965)
This study consists of two parts: a discussion of the housing situation in Britain followed by suggestions for reform. The book begins with a short history of British housing policy from the nineteenth century to the 1965.Having outlined the anomalies of the existing situation, the authors then specify remedies. They suggest a number of tax and mortgage-lending reforms that would enable prospective house purchasers to obtain larger loans and consequently to buy more expensive houses.
Includes bibliographical references.
usc 11/06/18
Loans
Keywords: Housing; Housing--Finance; Great Britain